Kebiasaan postur tubuh yang buruk yang mengganggu kesehatan sendi temporomandibula Bad posture habits that interfere with health of temporomandibular joint - Tine Martina Winarti; Rasmi Rikmasari (Journal of Dentomaxillofacial Science, 2011)
Temporomandibular joint (TMJ)is a component of the stomatognati system that supports oral dental health whichtheir components are closely interconnected. Posture is a habit that often do not realize that could cause animbalance in the joints and muscles, which in turn causes pain. Inadequate body posture can occur on sleepposition, lying down, sitting, walking, and other daily activities. Most people are not aware of the dangers of thesehabits. Dentists are expected to shed some light on the habits of this particular posture errors, which if not promptlyremoved, it will cause interference with stomatognati systems, such as joint and muscle pain, headache and neck.Complaints due to bad habits can be reduced significantly by eliminating the habit. So it is with the wrong posturehabits. With improved posture and a series of exercises as well as the care, the health of TMJ can return to normalwith minimal costs. This paper will put forward any posture that can lead to disruption of TMJ.